2010
DOI: 10.1016/j.respol.2010.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Public selection and financing of R&D cooperative projects: Credit versus subsidy funding

Abstract: a b s t r a c tIn this article we develop an analytical model of the selection process for R&D cooperative projects, to study the factors that motivate public project selection and corresponding funding, using two different financial instruments: subsidies and credits. For this purpose, we propose a three stage empirical strategy to analyse the differential individual effects of several factors on the decisions taken by the public agency. This analysis is based on project level data from cooperative R&D projec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 36 publications
0
42
0
5
Order By: Relevance
“…It seems clear that the establishment of many R&D cooperation agreements in the context of the Spanish manufacturing sector occurs as a result of the stimulus that many companies receive from the government (regional, national, and European). In this regard, in Spain, the share of public funds in the development of private R&D reaches the quota of 40% (Santamaría, Barge-Gil, and Modrego 2010).…”
Section: Resultsmentioning
confidence: 99%
“…It seems clear that the establishment of many R&D cooperation agreements in the context of the Spanish manufacturing sector occurs as a result of the stimulus that many companies receive from the government (regional, national, and European). In this regard, in Spain, the share of public funds in the development of private R&D reaches the quota of 40% (Santamaría, Barge-Gil, and Modrego 2010).…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, on the supply side, we focus on understanding whether the existence of creative and sustainable business ideas may affect the outcome of the selection of project proposals. There is an increasing body of literature on the allocation of external sources for start-ups (Santamaría et al 2010;Nofsinger and Wang, 2011). This also includes funding allocation for research projects in environmental sciences (Wellington and Lewis, 2016) and creativity (Feder and Katz-Gerro, 2012;Schnädelbach et al 2016).…”
Section: Inferential Analysismentioning
confidence: 99%
“…Research has shown that cooperation is not a determining aspect in project selection or funding (Santamaría et al, 2010), but plays a secondary role in supporting selection. In consequence, the concerted projects programme did not foster large consortia and often posed the problem of the free-riding behaviour of firms (Joost, 2003).…”
Section: Project-focused Policiesmentioning
confidence: 99%